Buddhism and coffee: the transformation of locality and non-human personhood in Southern Laos - Sprenger, Guido (Sojourn, 2018)
Among Jru' (Loven) uplanders in southern Laos, three different ecologies intersect. Animism focuses on local non-human persons like rice and earth spirits. Cash cropping elaborates translocal relationships with foreigners and technology, but reduces the extent of non-human personhood. Buddhism stresses both the translocal character and the transcendence of non-human persons. Villages are now in transition from subsistence swidden agriculture to coffee production and from animism to Buddhism. These two processes reinforce each other, as the question of non-human personhood defines both the differences and the potential conflicts between ecologies. The translocalization of local reproductive cycles thus conditions the decreased importance of non-humans as persons. (Sojourn/GIGA)